PENGARUH PENGALIHAN PP 46 2013 MENJADI PP 23 2018 TERHADAP TINGKAT PERTUMBUHAN WAJIB PAJAK UMKM DAN PENERIMAAN PPH PASAL 4 AYAT (2) DI KPP PRATAMA PASURUAN - Wahyu Suryani; Maslichah Maslichah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT            This research aims to know the influence of diversion PP 46 2013 be PP 23 2018 growth rate against the taxpayer acceptance of SME and income tax article 4 paragraph (2). This research included in the descriptive approach to quantitative. Data collection for this study using the method of documentation that exists in the KPP Pratama Pasuruan. Data analysis techniques used for hypothesis testing is to test the Mann Whitney Test are included in this category are nonparametric. The results of the analysis showed the growth rate of the taxpayer with the highest significance SME 0.814 more than 0.05 conclusion then no different from taxpayer SME growth rates before and after diversion PP 46 2013 be PP 23 2018. PPh acceptance of article 4 paragraph (2) with a value of less than 0.05 significance of 0.011 conclusion then no different from taxpayer SME growth rates before and after diversion PP 46 than 2013 be PP 23 2018.Key words: PP 46 2013, PP 23 2018, the growth of the taxpayer acceptance of SME, PPh Pasal verses (2)